Causes and Prevention of Failure in Varicose Vein Operations - Massell, Theodore B. (1973)
One hundred and one patients with poor results from the operative treatment of varicose veins were studied in an effort to determine the cause of the surgical failure. In a large majority, reoperation revealed that the primary cause of the poor result was the improper performance of the original operation. A smaller number of failures were due to errors in selecting the operative procedure. Relatively few poor results in long-term follow-up were attributable to the congenital predisposition to varicosity. When operation is properly planned and executed, it produces better long-term results than the injection compression therapy of varicose veins.